EVALUATING TELEMEDICINE UTILIZATION IN THE NATIONAL HOSPITAL USING RESOURCE PARAMETERS BASED ON THE AUSTRALIAN COUNCIL ON HEALTH CARE STANDARDS (ACHS) - Heenderi, Hendera; Setianto, Budhi; Adriansyah, Agus Aan (Universitas Nahdlatul Ulama Surabaya, 2024)
Digital transformation and disruptive innovation describe a comprehensive reorientation of industry including its business models due to the arrival of the digital technology era in the form of digitization of products, services and processes. Meanwhile, digital health products can be in the form of electronic health. The low utilization of Telemedicine visits is 2.90% of total visits as well as the conformity of NH Apps telemedicine products with ACHS standards. Analyzing the use of Telemedicine from Resource Parameters based on Australian Council on Healthcare Standards (ACHS) Standards at the National Hospital. The method for this research uses system theory (Input, Process and Output) and is descriptive research with a qualitative approach. By gathering information from 33 respondents who carried out analysis and assessment regarding the implementation of telemedicine in accordance with ACHS. Information that all telemedicine implementation in each department is going well except in the pharmacy department which is considered less good. The implementation of Telemedicine is in accordance with and meets the requirements in terms of the Use of Telemedicine Applications from the Australian Council on Healthcare Standards (ACHS) Requirements Aspect. Process Flow for Using Telemedicine in Hospitals. National Hospital Surabaya is running well and is systemized using the NH Apps application, divided into 2, namely the outpatient flow and the emergency treatment flow. Resources for Using Telemedicine Applications in Hospitals. National Hospital Surabaya has strong modalities regarding units and doctors are all involved in integrated services and have good assessments in system quality, information quality, service quality, structure and environment: